Harry Haft : Survivor of Auschwitz, Challenger of Rocky Marciano. - Haft, Alan (Religion, Theology and the Holocaust Ser., 2020)
Alan Scott Haft provides the firsthand testimony of his father, Harry Haft, a Holocaust victim with a singular story of endurance, desperation, and unrequited love. Harry Haft was a sixteen-year-old Polish Jew when he entered a concentration camp in 1944. Forced to fight other Jews in bare-knuckle bouts for the perverse entertainment of SS officers, Harry quickly learned that his own survival depended on his ability to fight and win. Haft details the inhumanity of the "sport" in which he must perform in brutal contests for the officers. Ultimately escaping the camp, Haft's experience left him an embittered and pugnacious young man. Determined to find freedom, Haft traveled to America and began a career as a professional boxer, quickly finding success using his sharp instincts and fierce confidence. In a historic battle, Haft fights in a match with Rocky Marciano, the future undefeated heavyweight champion of the world. Haft's boxing career takes him into the world of such boxing legends as Rocky Graziano, Roland LaStarza, and Artie Levine, and he reveals new details about the rampant corruption at all levels of the sport. --